How to think about emotion and morality: circles, not arrows. (October 2017) - Gray, Kurt; Schein, Chelsea; Cameron, C Daryl
Highlights: There are two frameworks for understanding conscious experience: arrows and circles. Arrows link one special mechanism to one unique mental experience. Circles explain mental experience as the overlap of more basic processes. Basic emotions and moral foundations advocate for arrows, constructionism for circles. We suggest that circles are a better way to think about emotion and morality. Abstract : Emotion and morality are powerful conscious experiences. There are two ways to think about their psychological basis: arrows and circles. Arrows ground each experience in its own specialized mechanism (mechanism x causes phenomenon x ; mechanism y causes phenomenon y ). Examples of arrows include when feelings of disgust are attributed to a specialized 'disgust circuit' and when judgments of impurity are attributed to a specialized 'purity foundation.' In contrast, circles — Venn diagrams — describe experiences as emerging from the overlap of more fundamental domain-general processes (different combinations of processes a, b, c cause both phenomena x and y ). Circles are used by constructionist theories of emotion and morality, including the Theory of Dyadic Morality, which grounds moral judgment in the combination of norm violations, negative affect, and perceived harm. Despite the intuitive popularity of arrows, we show that scientific evidence is more consistent with circles.